Brand Trust, Garansi Produk, dan Electronic Word of Mouth untuk mendorong Keputusan Pembelian Ban Merek Gama di Kota Surabaya - Putri Sesanti, Wiwit Ryzki; Abdul Halik (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to analyze the influence of Brand Trust, Product Warranty, and Electronic Word of Mouth on Purchase Decisions for Gama brand tires in Surabaya. The research adopts a quantitative method, involving a sample of 100 respondents who purchased Gama brand tires at CV BanQ Tangguh Perkasa. Data were collected using a questionnaire with a Likert scale. The data analysis techniques include Instrument Testing, Classical Assumption Testing, and Hypothesis Testing. The results show that all research indicators are valid and reliable. Based on Multiple Linear Regression analysis, Product Warranty exerts the most dominant influence on Purchase Decisions, while Brand Trust has the lowest impact. The T-test indicates that Product Warranty significantly affects Purchase Decisions, whereas Brand Trust and Electronic Word of Mouth do not have significant effects. Simultaneously, all three variables influence Purchase Decisions with an R² value of 48.2%, meaning 52.8% is influenced by other factors outside the scope of this study. This research recommends future studies adopt qualitative methods to explore consumers' reasons behind purchase decisions. Additionally, including variables such as product quality, price, or promotion is suggested to broaden the study. Expanding the sample size is also advised to enhance the validity and generalizability of the findings. Keywords: Brand Trust, Product Warranty, Electronic Word Of Mouth, Purchasing Decisions.